Making sense of subclinical cardiac alterations in patients with diabetes - Manan Pareek; Michael Hecht Olsen (Biomolecules & Biomedicine, 2019)
Patients with diabetes are prone to develop a distinct primary myocardial condition, diabetic cardiomyopathy, placing them at an increased risk for heart failure [1-3]. This occurs independently of hypertension, coronary artery disease, and other established causes of heart failure. Pertinent findings include increased mass, concentric changes, and diastolic dysfunction of the left ventricle [4,5]. Such adverse remodeling is common among patients with diabetes and appears to be strongly associated with its duration, suggesting a role for persistent metabolic stress [6-8]. However, which exact components of the diabetic syndrome determine these cardiac alterations is not clear. Moreover, most studies have investigated patients with type 2 diabetes, and it is uncertain whether patients with type 1 diabetes experience similar myocardial changes.